Student Readiness for AI in Business: Roles of Literacy, Attitude, and Practical Engagement - Kuncoro Hadi; Sisca Debyola Widuhung; Nuraini Nuraini (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Purpose: This study investigates the determinants of student readiness for artificial intelligence (AI) integration in business education, emphasizing the roles of AI literacy, affective attitude, and practical engagement. The research addresses the increasing demand for future business professionals equipped to operate in AI-enhanced environments.Methodology: A quantitative approach was employed using survey data from 177 undergraduate students in the Greater Jakarta area. Constructs were measured through validated instruments and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine both direct and mediated relationships among variables.Findings: The results show that AI literacy and affective attitude have significant direct effects on AI readiness. Practical engagement contributes to readiness indirectly through affective attitude. Affective attitude is the strongest direct predictor of readiness and significantly mediates the effects of AI literacy and practical engagement.Conclusion: The findings suggest that enhancing AI readiness requires a holistic educational framework integrating conceptual knowledge, experiential exposure, and emotional receptivity. Curriculum designers should focus on affective learning strategies alongside technical training to foster a workforce capable of navigating AI-driven business contexts.